Stress magnitudes in the Basel enhanced geothermal system - Valley, Benoît; Evans, K. F. (My University, 2019)
This paper presents the results of an evaluation of stress magnitudes in the granitic EGS reservoir in Basel, Switzerland. The profile of minimum principal horizontal stress, Shmin, is constrained by hydraulic tests, but the magnitude of the maximum horizontal principal stress, SHmax is uncertain. Here we derive estimates for SHmax by analysing breakout width data from an acoustic televiewer logs run in the granitic basement section of the BS-1 borehole. Some 81% of the borehole in the granite is affected by breakouts. The approach employed to derive SHmax magnitude from the estimated breakout widths is taking into account all stress components at the borehole wall including the remnant thermal stress arising from the cooling of the borehole wall by the drilling. In BS-1, breakouts width tends to decrease with depth. Assuming there is no significant systematic change in the strength characteristics of the rock along the length of the hole, for which there is no evidence, the large-scale trend has the consequence of implying a small gradient of the SHmax profile. A low Shmin gradient was also implied by a stress analysis that additionally considered the occasionally coincident presence of drilling induced tension fractures. The absolute values of SHmax depend upon the failure criterion used. Criteria that consider the strengthening effect of the intermediate stress (Mogi-Coulomb and Hoek-Brown 3D) yield profiles that violate frictional limits on the strength of the crust above 4 km, whereas the profiles of the Mohr-Coulomb and Rankine criteria do not. The Mohr-Coulomb criteria profiles indicate a trend in SHmax from favoring strike-slip faulting above 4200 m to strike-slip/normal faulting below. This is consistent with focal mechanisms recorded during the reservoir stimulation which show a mix of strike-slip and normal faulting throughout the depth range considered.